Peningkatan Kemampuan Ekspresi Diri Melalui Bimbingan Konseling Pendekatan Gestalt: Studi Kasus Seorang Siswa di SMP - Lestari, Catur Indah; Latief, Suciani (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2025)
The ability to express oneself is a crucial aspect of psychological development in junior high school students. Many students face difficulties in articulating their feelings and thoughts, which are often influenced by internal factors like emotional instability and external factors like family conditions. This study examines the impact of applying the Gestalt approach in improving the self-expression skills of students at SMP Negeri 23 Penajam Paser Utara. Using a case study method, this research focuses on an 8th-grade student who experienced a significant behavioral change due to his parents' divorce. Data was collected through observations, in-depth interviews, and questionnaires, then processed using qualitative thematic analysis. The research findings indicate that Gestalt techniques, such as empty chair and role-playing, are effective in helping students recognize, understand, and express their feelings more effectively. The student, who was initially quiet and withdrawn, began to show improvement in communication skills, confidence in expressing opinions, and social participation after several counseling sessions. Thus, the Gestalt approach can be an effective way to support the development of students' self-expression skills.